2016
DOI: 10.1093/femsyr/fow062
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of diacylglycerol acyltransferase inYarrowia lipolyticaaffects lipid body size, number and distribution

Abstract: In the oleaginous yeast Yarrowia lipolytica, the diacylglycerol acyltransferases (DGATs) are major factors for triacylglycerol (TAG) synthesis. The Q4 strain, in which the four acyltransferases have been deleted, is unable to accumulate lipids and to form lipid bodies (LBs). However, the expression of a single acyltransferase in this strain restores TAG accumulation and LB formation. Using this system, it becomes possible to characterize the activity and specificity of an individual DGAT. Here, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Similarly, the overexpression of diacylglycerol acyltransferase increased the lipid content from 13% to the range of 39-53% of the DCW in the strain without active PEX10 [58]. Other studies have attempted DGA1 or DGA2 overexpression strategy to enhance lipid content in this yeast [3,[54][55][56][57]. Overall, overexpression of DGA genes increased lipid content while decreasing biomass formation in the HPDD strain due to LEU2 deletion.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, the overexpression of diacylglycerol acyltransferase increased the lipid content from 13% to the range of 39-53% of the DCW in the strain without active PEX10 [58]. Other studies have attempted DGA1 or DGA2 overexpression strategy to enhance lipid content in this yeast [3,[54][55][56][57]. Overall, overexpression of DGA genes increased lipid content while decreasing biomass formation in the HPDD strain due to LEU2 deletion.…”
Section: Discussionmentioning
confidence: 85%
“…In the final step of the TAG synthesis pathway, DGA1, YALI0E32769g on the lipid droplet (LD) membrane, and DGA2, YALI0D07986g in the ER, play prominent roles in acylation of diacylglycerol to produce TAG, which is stored in LDs especially during the stationary phase [49][50][51]. Therefore, the overexpression of DGA1 and DGA2 results in enhanced lipid accumulation [3,[52][53][54][55][56][57][58][59]. TAG synthesis and remobilization is a dynamic process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, enhanced lipid production in cells expressing AtDGAT1 was observed in other hosts such as insect cells , A. thaliana , and canola . Furthermore, DGAT genes from other sources such as fungi Saccharomyces cerevisiae and Yarrowia lipolytica , plants such as Macadamia tetraphylla , and Brassica napus showed enhanced TAG or oil production but to varying degrees. The variable performance of the different DGAT genes may be caused by inherent differences in enzyme activities or host interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported by Tran, Breuer, et al (), who transformed S. cerevisiae H1246 using EaDAcT isolated from Euonymus alatus . It was previously observed that the insertion of native DGA1 or DGA2 acyltransferase genes (Gajdoš, Ledesma‐Amaro, Nicaud, Čertík, & Rossignol, ) and DGAT2 gene from mouse (Ledesma‐Amaro, unpublished data) into the Q4 mutant of Y. lipolytica under the control of a strong promoter was able to trigger lipid accumulation at an even higher rate than the wild type. This strongly indicates that DAcT plays a different function to the TAGs‐producing acyltransferases.…”
Section: Discussionmentioning
confidence: 96%